Echoes from the Margins: Exploring Minor Characterizations in Kanthapura - Dr.Devi Bhushan (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
Raja Rao’s magnum opus, Kanthapura, is widely celebrated for its rich tapestry of characters and its profound exploration of the Indian independence movement. While the central characters, such as Moorthy and Ratna, have received substantial critical attention, the minor characters in the novel have often been overlooked. This research paper aims to shed light on the significance of these minor characters and their contribution to the larger narrative. Through a close examination of the portrayal and function of minor characters, this study uncovers the nuanced ways in which they shape the thematic and structural elements of Kanthapura. The paper argues that the minor characters, though seemingly peripheral, serve as crucial echoes from the margins, amplifying the novel’s central themes of community, resistance, and the complexities of social change. By analyzing the diverse range of minor characterizations, from the elderly Rangamma to the young Seenu, this research illuminates the multifaceted ways in which Rao’s masterpiece engages with the lived experiences of ordinary individuals caught in the throes of a transformative historical moment.